Capture the flag: local factionalism as electoral mobilization in dominant party Uganda. Issue 8 (17th November 2019) - Wilkins, Sam
ABSTRACT: This article addresses a question relevant to many non-democratic regimes: how can a successful dominant party be an institutionally weak one? President Yoweri Museveni and his National Resistance Movement (NRM) have dominated Ugandan politics since coming to power in 1986. However, the NRM does not possess many of the institutional endowments that other dominant parties use to control mass and elite politics, such as central control of candidate selection, autonomous mobilizing structures, or dispensation of sufficient political finance to its candidates. Instead, the party secretariat has no real institutional power independent of the personalist Museveni regime, and its local branches house fierce internal competition each election in which most incumbents lose office. This article argues that the NRM mobilizes so well for Museveni despite its institutional deficits due to the precise nature of the competitive process its local elites go through to win its nomination (or "flag") and the subsequent general election. This process sees self-organized and self-financed candidates and their factions rejuvenate the party and mobilize votes for the concurrent presidential election as a by-product of their competition with one another. The article makes this argument with qualitative data from three districts gathered during the 2016 elections.